A directionally evolved genomic feature in BRSK2 harbors divergent alleles in neurocognitive disorders - M. Ohadi; H. Bayat; S. Khamse; A. Delbari; M. Arabfard (Scientific Reports)
Abstract The human Brain-specific Serine/Threonine Kinase 2 (BRSK2), alternatively known as Synapses of Amphids Defective (SAD)-A, is mainly expressed in the brain, and required for neuronal polarization and differentiation. This gene contains the longest 5′ untranslated region (5′ UTR) pentanucleotide short tandem repeat (STR), (CGGCT)6, in human. We hypothesized that this exceptional length may confer selective advantage in cognitive functioning in human. The region spanning (CGGCT)6 was sequenced in a sample of 339 unrelated individuals, consisting of cases affected by late-onset neurocognitive disorder (NCD) (N = 163) and matched controls (N = 176). Consequently, we mapped CGGCT motifs and STRs across the human genome and obtained the phylogenetic tree of the BRSK2 sequence spanning the CGGCT STR in 19 species belonging to several orders of mammals, including Rodents, Carnivora, Artiodactyls, Perissodactyla, and Primates. We found that (CGGCT)6 was part of a complex island of 17 consecutive CGGCT motifs/STRs, ranging from 1 to 6-repeats, stretching the BRSK2 core promoter and 5′ UTR. Across the human genome, the CGGCT island was unique with respect to density, complexity, and repeat length of CGGCT motifs and repeats. This island was flanked by a 5′ UTR CGG STR in its downstream. The evolution of the CGGCT island mainly coincided with the phylogenetic distance of the species studied, and the CGG STR was primate-specific, suggesting directional, rather than random evolution of this complex sequence. While (CGGCT)6 was strictly monomorphic in the human samples studied, a 7-repeat of this motif was detected in the controls only. In another CGGCT repeat inside the CGGCT island, there was a significant excess of homozygosity for a long allele (4-repeat) in the controls (Mid-P = 0.02). At the same locus, a 3-repeat allele was detected in the NCD group only. Additionally, alleles were detected at the extreme short and long lengths of the CGG STR in the NCD group only. Probable diagnosis in the patients harboring divergent genotypes spanned Alzheimer’s disease and vascular dementia. We report a novel genomic feature, consisting of a CGGCT motif/STR island, and a CGG STR in BRSK2 that coincide with directional evolution of several orders of mammals. Several polymorphic and rare alleles were divergently distributed in the NCD and control groups across this region, which may reflect a possible link with cognitive functions in human.